FROM CONCRETE MOVEMENT TO CLIPOEMA: POETRY IN THE HISTORY OF BRAZILIAN ART: a poética na história da arte brasileira (TEL Tempo, Espaço e Linguagem, 2021)
Clipoemas are works of art that interrelate sound, verbal and visual languages. They originate in Concrete and Neoconcrete poems and enhance contemporary multimedia production. The article historically contextualizes the Concrete and Neoconcrete Movement that emerged in Brazil in the 1950s, in order to explain the unique characteristics of the production of Clipoemas in the 1990s.Keywords: Clipoemas. Concretism. Neoconcretism. Visual culture. Art history.